Adoption of Mechanization by Paddy Growers in RJKIP Project Command Area, Kailali - Nepali, Nabin; Ghimire, Milan; Pandey, Prem; Lamsal, Sijan (Journal of Tikapur Multiple Campus, 2026)
This study aims to assess the mechanization status and constrains faced by the rice growing farmers and its impact in paddy production in Kailali district. The study was conducted in command area of RJKIP which covers Tikapur municipality, Lamki-Chuha municipality and Janaki rural municipality which were purposively selected. Sampling of 92 rice growers was done using simple random sampling method and primary data was collected via household survey. Multiple linear regression model was used to analyze the factors affecting adoption of mechanization among rice growers. The findings showed education level, larger land holdings, income of farmers had significantly increased the adoption of mechanization where, age, family size and labour cost had negative effect on adoption. Major problems in adoption of mechanized agriculture system were higher cost of machine followed by lack of technical knowledge, small land holdings, lack of subsidy etc. Farm mechanization can be enhanced by providing subsidy on machineries, technical assistance on using different tools and farming practices followed by land management scheme.